The influence of organic and inorganic nutrient inputs on soil organic carbon functional groups content and maize yields. Issue 8 (August 2021) - Ndung'u, M.; Ngatia, L.W.; Onwonga, R.N.; Mucheru-Muna, M.W.; Fu, R.; Moriasi, D.N.; Ngetich, K.F.
Abstract: Locally available organic inputs to soil, solely or in combination with inorganic fertilizers, are used to reverse declining soil fertility and improve soil organic matter content (SOM) in smallholder farms of most Sub-Saharan Africa (SSA) countries. Soil organic matter characterization can indicate soil organic input, carbon (C) sequestration potential, or even an authentication tool for soil C dynamics in C stocks accounting. This study determined the effects of the long-term application of selected integrated soil fertility management (ISFM) technologies on SOM functional group composition and maize yields. The study was carried out on an ongoing long-term soil fertility field experiment established in 2004 in Mbeere South sub-county, the drier part of upper Eastern Kenya. The experimental design was a randomized complete block design. The ISFM treatments were 60 kg ha −1 nitrogen (N) from goat manure (GM60); 30 kg ha −1 inorganic N fertilizer (IF30); 60 kg ha −1 inorganic N fertilizer (IF60); GM30+IF30; 90 kg ha −1 inorganic N fertilizer (IF90); 60 kg ha −1 N from lantana (Lantana camara) (LC60); LC30+IF30; 60 kg ha −1 N from mucuna beans ( Mucuna pruriens) (MP60); MP30+IF30; 60 kg ha −1 N from Mexican sunflower ( Tithonia diversifolia ) (TD60); TD30+IF30, and a control with no inputs. The C compositions of ground soil samples and organic amendments were analyzed using 13 C solid-state NMR. The GM60, GM30+IF30, LC60, and TD60 treatments had much higher Alkyl and O-Alkyl C SOM functional groups than the control and other treatments. The average soil C for the control was 7.47 mg kg −1 and ranged from 5.03 to 7.37, 9.57 to 18.77, and 7.03–14.50 mg kg −1 for inorganic fertilizers, organic fertilizers, and organic + inorganic fertilizers, respectively. The mean grain yield for the control was 0.56 Mg ha −1 and ranged from 1.51 to 1.99, 1.94 to 4.16, and 2.98–4.60 Mg ha −1 for inorganic fertilizers, organic fertilizers, and organic + inorganic fertilizers, respectively. The results showed that a long-term application of sole organic fertilizers or combined with inorganic fertilizers increases maize yield and soil C sequestration potential. The increase was attributed to high Alkyl and O-Alkyl C SOM functional groups. Hence, knowing the C fraction content of organic inputs is vital in determining the best-fit management technologies for ameliorating soil fertility and sustaining and/or improving crop yields. Abstract : Grain yield; Carbon sequestration; Organic amendments; Soil carbon fractions; Soil fertility.